(untitled) (The South Asianist Journal, 2015)
With reference to their portrayals of Partition, I discuss the value of Kamal Haasan’s Hey Ram! (2000), Rakeysh Omprakash Mehra’s Bhaag Milkha Bhaag (2013), and M. S. . Sathyu’s Garam Hawa (1973) as historical resources. I emphasize how the ‘othering’ of Muslims in Hey Ram! and Bhaag Milkha Bhaag finds expression in terms of masculinity and Indian patriotism. Drawing on Vasudevan’s (2002) critique of Hey Ram!, I argue that Kamal Haasan does not offer viewers sufficient distance from the film’s Hindu-extremist protagonist, thus curbing their ability to critique the Hindutva historical narrative portrayed. Further, Haasan’s intended dismissal of this Hindutva narrative of Hindu loss and Muslim murder falls short due to its portrayal of the film’s central Muslim character as relatively effeminate and in need of Hindu paternalism. Similarly, Muslim-Hindu relations (as well as national anxieties about Indian identity and culture) are configured through a play between masculinities in biopic Bhaag Milkha Bhaag, as commented upon by Kumar (2014). Through a track-and-field victory in Pakistan, Milkha redeems the emasculation caused by his flight from the Punjab during Partition. I discuss Garam Hawa as a counterpoint to Hey Ram! and Bhaag Milkha Bhaag, both of which I read as mostly congruous with secular official historiography. In addition to presenting the perspective of members of the Indian Muslim minority that stayed behind after Partition, Garam Hawa digs up financial and sentimental motives for belonging in India that are absent from the official historical narrative of Partition.